Impact of nontariff barriers on Latin American agroexports (20182023) - Alvarado Pacaya, Maria F. (2024)
Objective. Identify the impact of nontariff barriers on agroexports of Latin America in the Scopus, Redalyc, Web of Science, and Proquest databases, during the years 2018 2023. Methods. A systematic review was carried out, resulting in 158,339 records, of which 18 were selected for subsequent analysis, following exclusion and inclusion criteria. Results. The results reveal information such as the name of the authors, year of publication, the title of the record, country of origin of the research, type of study, method, and sample used, as well as the results and conclusions obtained by the original authors. Conclusions. In relation to the studies analyzed, it has been found that there is a positive impact ofsanitary and phytosanitary measures (SPS), if compared with other barriers.